Characterisation of fatty acid, carotenoid, tocopherol/tocotrienol compositions and antioxidant activities in seeds of three Chenopodium quinoa Willd. genotypes. (1st May 2015) - Tang, Yao; Li, Xihong; Chen, Peter X.; Zhang, Bing; Hernandez, Marta; Zhang, Hua; Marcone, Massimo F.; Liu, Ronghua; Tsao, Rong
Highlights: First report of the existence of lutein and zeaxanthin in different quinoa seeds. Composition of all fatty acids, carotenoids, tocopherols and tocotrienols in different quinoas. Darker quinoa seeds had significantly higher levels of lipophilic bioactives. Lipophilic compounds contribute significantly to the antioxidant activities. Quinoa is a good dietary source of lutein, γ-tocopherol and omega-6/omega-3 ratio. Abstract: Composition of fatty acids, tocopherols, tocotrienols, and carotenoids, and their contribution to antioxidant activities were investigated in seeds of three coloured quinoa cultivars (white, red and black). The major components and individual compounds were significantly different, and their concentrations were higher in darker seeds ( p < 0.05). The oil yield was 6.58–7.17% which contained predominantly unsaturated fatty acids (89.42%). The ratio of omega-6/omega-3 fatty acid was ca. 6/1. The total tocopherol content ranged from 37.49 to 59.82 μg/g and mainly consisted of γ-tocopherol. Trace amount of α- and β-tocotrienols was also found. Black quinoa had the highest vitamin E followed by red and white quinoas. Carotenoids, mainly trans -lutein (84.7–85.6%) and zeaxanthin were confirmed for the first time in quinoa seeds, and the concentration was also the highest in black seeds. The antioxidant activities of lipophilic extracts were positively correlated with polyunsaturated fatty acids, total carotenoids and total tocopherols.